Dermatological Publications from Nepalese Dermatologist Before and During the COVID-19 Pandemic Period: A Review - Parajuli, Niraj; Chapagai, Badri; Paudel, Sushil (Nepal Journal of Dermatology, Venereology & Leprology, 2023)
Introduction: The COVID-19 pandemic created a nation-wide lockdown with hospital services resorting only to the emergency sections. Dermatology out-patient was closed with majority of services being deferred for a later date or through online platform. Here, we try to find whether Nepalese dermatologists were contributing to sciences through research. Methods: A Google Scholar search using certain key words to search for publications done by Nepalese dermatologist during the pandemic was done for year 2020-2021 described as pandemic period. Similar search was conducted for year 2018-2019 for the same time frame called as pre-pandemic. All the publications were analyzed using appropriate statistical methods. Results: A total of 197 publications were retrieved for pandemic period as compared to only 106 published articles in the non-pandemic period. Among 197 publications, 81 (41.11%) were published in PubMed indexed journal as compared to only 40 (37.73%) publications out of 106 total publications during the earlier period. However, the increase in the number was not statistically significant. Conclusion: An interest among Nepalese dermatologists for academic publications was noted during the pandemic period. This might be due to the proper use of time during the lockdown and closure of out-patient department.